The clinical manifestations of nervous system mesenchyme syphilis - T. A. Valikova; V. M. Alifirova; I. M. Fyodorova; N. Yu. Paimursina (Бюллетень сибирской медицины)
Nervous system syphilis — neurosyphilis (NS) belongs to rather rare diseases. According to the different authors data available it comes to about 1% of the nervous system organic disturbances and develops by 5—10% syphilous patients not having been treated in the acute stage of the pathological process. The syphilitic disturbance of the nervous system is a chronic progressive disease caused by the pale spirochaeta. The nervous system disturbance occurs basically in two ways: secondary one, because of brain shells, vessels, gummatous manifestations involving in the pathologic process; or primary one, when the causative agent affects directly the brain substance. In the first case syphilis is called rnesodermic or early one; in the second case — parenchymatous or late, primary one. In the article the analysis of two clinical cases of mesenchyme neurosyphilis is carried out: latent neurosyphilis and syphilitic meningomyelitis. Neurosyphilis classification is applied to clinical manifestatons of syphilitic arachnoiditis and vasculitis are described. The methods of specific and nonspecific therapy of mesenchyme syphilis are stated in detail.